Determination of healthy natural antioxidants in selected muskmelon (Cucumis melo) cultivars - IMEN, HENANE; ANISSA, RIAHI; IMEN, TLILI; CHAFIK, HDIDER (The Indian Journal of Agricultural Sciences, 2023)
Muskmelon (Cucumis melo L.) is a popular summer fruit consumed all over the world due to the combination of refreshingly sweet taste, pleasant flavour and nutritional value. Melon fruit is characterized by germplasm variability with superior quality. This study aimed to evaluate 5 promising local muskmelon cultivars (Maazoun, Galaoui, Stambouli, Trabelsi, Asli) for some physicochemical characteristics, the content of different bioactive compounds and the antioxidant activity. The experiments were conducted for two consecutive years 2018 and 2019 at the support station of the inter-professional vegetable group positioned in the North East of Tunisia. Significant differences were observed across the melon cultivars (P<0.05) for soluble solids (9–12°Brix), pH (5.5–6.6), carotenoid (7.5–59.5 mg/ kg FW), phenolic (400–1390 mg GAE/kg FW), flavonoid (251.3–390 mg RE/kg FW), vitamin C (138.2–193 mg/kg FW) contents, as well as hydrophilic (102.28–285.43 μM Trolox/100 g FW) and lipophilic (30–180.22 μM Trolox/100 g FW) antioxidant activities. Galaoui showed the highest levels of carotenoids, phenolics, flavonoids, vitamin C and antioxidant activities followed by Stambouli. Trabelsi cultivar also had a high level of flavonoids. The enhanced hydrophilic antioxidant activity in Galaoui was significantly correlated to phenolic content (r = 0.91). These findings proved that besides being refreshing summer fruit, muskmelon can be considered a promising healthy produce with a superior potential source of natural antioxidants.